Pengaruh Struktur Organisasi Terhadap Perilaku Warga Sekolah SPNF SKB SIKKA - Elisabeth Henderika Dua Neang; Maria Materdey Kero Wara; Katharina Woli Namang (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Organizational structure has the consequence of changing the behavior and characteristic values of the people in the organizational structure. Organizational structure is a behavioral controller. Changes to the organizational structure are certainly intended as an effort to change behavior. This study aims to examine the influence of organizational structure on student behavior. Using qualitative methods, this research involves direct observation and interviews with various stakeholders in the school. The results of the study show that SPNF SKB SIKKA implements a hierarchical organizational structure with unit heads, deputies, teachers and tutors. This study aims to determine the influence of organizational structure on the behavior of non-formal education schools. After research, it can be concluded that the hierarchical structure of the SPNF SKB SIKKA school organization creates an orderly and disciplined environment but also presents challenges in terms of flexibility, initiative and participation active and also have a clear framework of vision, mission and goals to realize an early childhood education unit and education in the community that answers the learning needs of the community and makes an education unit that provides the widest possible opportunity for the community to obtain education.